If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + -4x = 13 + -10x Solving 43 + -4x = 13 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 43 + -4x + 10x = 13 + -10x + 10x Combine like terms: -4x + 10x = 6x 43 + 6x = 13 + -10x + 10x Combine like terms: -10x + 10x = 0 43 + 6x = 13 + 0 43 + 6x = 13 Add '-43' to each side of the equation. 43 + -43 + 6x = 13 + -43 Combine like terms: 43 + -43 = 0 0 + 6x = 13 + -43 6x = 13 + -43 Combine like terms: 13 + -43 = -30 6x = -30 Divide each side by '6'. x = -5 Simplifying x = -5
| 3x^3-x^4= | | -2-y=-8 | | 8(4x-8)=4(8x+7) | | log(x-3)+log(x-1)=log(3x-7) | | x(x+9)=4x+6 | | 40x^2-23x-30= | | -3(-7v+3)+8v=5v-r | | 8(2q-4)+5(q+11)=65 | | 24x^2+2x-15= | | 8y-7(1)+3=-4(1)+5y-9 | | x=50-(10/3)y | | (7x+8)+(x-22)=2 | | 2x=5x-180 | | 5x^2=11x+36 | | 3b-0.9=4b | | 4cos^4x-5cos^2x+1=0 | | -8y+8=-80 | | 81+99.4= | | 2(n+4)=7n-1 | | 9(13.6)-23= | | x-10=22.36 | | 12+4x=48 | | 3y+3y=5y+1 | | 5(13.6)+13= | | 6-4x=6x-8+4+2 | | 10uv^2(3u-v)+12u^2v(v-3u)= | | -4w^2+8w+5=0 | | (3x)-(4y)=(12) | | 4x=13x-21 | | f(x)=-0.25x^4+2.25x^2+x-3 | | -4(2x-6)-12x=-6 | | 0=6x^2+30x-84 |